Implementation of Pro Bono Notary Legal Services for the Poor in Grobogan Regency - Utami, Dwi Risky Faulam; Riyanto, Taufan Fajar (Jurnal Konstatering, 2025)
Indonesia, as a country based on law as mandated in Article 1 paragraph (3) of the 1945 Constitution, stipulates that all aspects of national and state life must be based on law. This country based on law requires the protection and fulfillment of legal rights for all citizens without exception, including the right to legal aid. Within the framework of this country based on law, the role of notaries as public officials who carry out part of the state's functions is very important, especially in providing fair and equitable legal services. The author conducted the research with the aim of finding out and analyzing the implementation of the provision of free pro bono notary legal services in Grobogan Regency and analyzing what obstacles were encountered when implementing pro bono notary services. To find out the above objectives, the author used an empirical legal research type. Data sources were obtained from several stages, namely through field research (interviews) and library research. Data analysis in a systematic manner includes data reduction, data presentation and drawing conclusions. Based on the research results, it was concluded that the legal regulations regarding the notary's obligation to provide free legal services to the poor are contained in Article 37 paragraph (1) of the UUJN and Article 3 paragraph (7) of the Notary Code of Ethics. In practice, Notary Mulyono, S.H., M.Kn has carried out his obligations in accordance with the provisions of the Notary Law, legal services are not only provided to poor clients but also provided for foundation activities, activities in the social, humanitarian and religious fields. Notaries assess the poor based on humanity and conscience. Meanwhile, the obstacles encountered are that the provisions in Article 37 paragraph (1) of the UUJN do not explain in detail the procedures and who is said to be able to receive legal assistance to determine whether someone is eligible or can be exempted from fees, and there is still a lot of stigma in society considering that notary services are very high.